Analysis of Fitting Growth Models in Jinghai Mixed-Sex Yellow Chicken - Yang, Y.; Mekki, D.M.; Lv, S.J.; Wang, L.Y.; Yu, J.H.; Wang, J.Y. (International Journal of Poultry Science, 2006)
The three nonlinear curves of Logistic, Gompertz and Bertalanffy model were used to fit the growth model in Jinghai Yellow chicken of different sex. The results indicated that the three growth models were well fitted the prediction of growth parameters. Females reached inflexion point at earlier age than males; however, their body weight was significantly lighter than males. Inflexion body weight were 1098.99, 1161.86 and 1392.91 g for males and 824.29, 827.99 and 918.67 for female estimated from Logistic, Gompertz and Bertalanffy models, respectively. Fitting degrees (R2) for the three models were higher than 99%. The lower X2 values estimated were 9.22 and 7.43 from Bertalanffy model for males and females respectively indicated that, Bertalanffy model was the best model fitted growth prediction parameters of Jinghai Yellow chicken.